Pendugaan Potensi Air Tanah Menggunakan Instrumen Aidu Golden Rod (Implementasi di Pesantren Alfahmu Kecamatan Tambang, Kabupaten Kampar, Provinsi Riau): Implementasi di Pesantren Alfahmu Kecamatan Tambang, Kabupaten Kampar, Provinsi Riau - Riady, Azhar; Ikhlas, Hari Firman; Yusa, Muhammad; Suprayogi, Imam; Sandhyavitri, Ari (LPPM UMRI, 2026)
Pesantren Alfahmu, located in Tambang District, Kampar Regency, Riau Province, faces significant challenges in securing a reliable clean water supply for its students and daily operations. This community service activity aimed to assess groundwater potential at three strategic locations within the pesantren premises using the AIDU Golden Rod (AGR) geophysical instrument. The survey was conducted along four measurement lines across three points: the mosque/musholla area, the dormitory and classroom area, and the drinking water depot and ablution area. Data were processed and interpreted using AIDU Prospecting software with multiple configurations (Configuration-0, Configuration-1, and Configuration-2). Results indicate that all surveyed areas have viable aquifer potential. Confined aquifers were consistently identified at depths of 165–300 meters at all three points, offering more stable and sustained water supply compared to shallow free aquifers (0–50 m depth) which are highly influenced by rainfall. Recommended drilling depths range from 165–275 meters with screening pipes installed at appropriate depths. The mosque/musholla area is recommended as the primary centralized drilling location due to its strategic central position. Pre-test and post-test questionnaire results showed a significant increase in participants’ understanding from 8% to 75%.